Clinical Presentation of Preeclampsia and the Diagnostic Value of Proteins and Their Methylation Products as Biomarkers in Pregnant Women with Preeclampsia and Their Newborns - Maria Portelli; Byron Baron (Journal of Pregnancy)
Preeclampsia (PE) is a disorder which affects 1-10% of pregnant women worldwide. It is characterised by hypertension and proteinuria in the later stages of gestation and can lead to maternal and perinatal morbidity and mortality. Other than the delivery of the foetus and the removal of the placenta, to date there are no therapeutic approaches to treat or prevent PE. It is thus only possible to reduce PE-related mortality through early detection, careful monitoring, and treatment of the symptoms. For these reasons the search for noninvasive, blood-borne, or urinary biochemical markers that could be used for the screening, presymptomatic diagnosis, and prediction of the development of PE is of great urgency. So far, a number of biomarkers have been proposed for predicting PE, based on pathophysiological observations, but these have mostly proven to be unreliable and inconsistent between different studies. The clinical presentation of PE and data gathered for the biochemical markers placental growth factor (PlGF), soluble Feline McDonough Sarcoma- (fms-) like tyrosine kinase-1 (sFlt-1), asymmetric dimethylarginine (ADMA), and methyl-lysine is being reviewed with the aim of providing both a clinical and biochemical understanding of how these biomarkers might assist in the diagnosis of PE or indicate its severity.